Fatwa and the Sound Horeg Question: Contesting Rights, Noise, and Social Order in East Java, Indonesia - Muhammad Fauzinudin Faiz; Arifki Budia Warman; M Syamsul Huda; Agus Aditoni; Yassine Chami; Haris Maiza Putra; Wildan Miftahusurur (Universitas Islam Negeri Raden Intan Lampung, 2026)
This article investigates the “sound horeg question” in East Java, a socio-legal controversy concerning the definition, justification, restriction, and governance of excessive public sound through Islamic legal authority. Although fatwas have increasingly addressed environmental and technological problems, their role in regulating auditory pollution and technologically amplified cultural practices remains insufficiently examined. Sound horeg, referring to high-powered audio systems used at social celebrations and street events, has generated significant public debate concerning excessive noise levels, potential health risks, public disturbance, property-related harm, and practices perceived as contrary to religious norms. In response, the East Java branch of the Indonesian Ulama Council issued Fatwa No. 1 of 2025, declaring certain harmful uses of sound horeg to be ḥarām on the basis of Islamic legal principles and empirical considerations. Employing a qualitative socio-legal approach and hermeneutic content analysis, this article examines the fatwa alongside Indonesian environmental regulations, medical literature on noise exposure, public debates, and classical Islamic legal sources. The analysis demonstrates that the fatwa not only extends Islamic legal reasoning to auditory pollution but also reframes excessive sound as a normative issue involving harm, public welfare, morality, and the legitimate use of public space. By employing maqāṣid al-sharīʿah and legal maxims such as lā ḍarar wa lā ḍirār, the fatwa performs a quasi-regulatory function within Indonesia’s plural legal landscape. Although formally non-binding, it provides religiously authoritative criteria for negotiating competing claims concerning cultural expression, public health, collective rights, and social order. This study contributes to scholarship on Islamic law and society by demonstrating how fatwas respond to emerging sociotechnical disruptions and participate in the normative governance of public life.